Quantitative Muscle MRI as Outcome Measure in Patients With Becker Muscular Dystrophy—A 1-Year Follow-Up Study - Sheikh, Aisha M.; Rudolf, Karen; Witting, Nanna; Vissing, John (Frontiers in Neurology, 2021)
Introduction: With the advent of emerging molecular therapies for muscular dystrophies, the need for knowledge about natural history course of such diseases is of the utmost importance in the preparation for future trials. However, for Becker muscular dystrophy such knowledge is scarce. Objective: In this 1-year follow-up study, we examined disease progression in Becker muscular dystrophy by monitoring changes in MRI-assessed muscle fat fraction (FF) in axial and lower limb muscles and quantitative muscle strength of axial muscles . Methods and materials: Sixteen patients with Becker muscular dystrophy were investigated by; 1) muscle strength of the trunk using a Biodex dynamometer, 2) Dixon muscle MRI of paraspinal and lower limb muscles. Quantitative MRI data was analyzed in two parts: First part consisted of all participants (N = 16). The second analysis assessed two separate groups comprising lesser affected participants (N = 5) and more severely affected patients (n = 11). Results: Trunk extension and flexion strength remained stable from baseline to follow-up. MRI did did not show any significant increase in muscle FF % from baseline to follow-up in all patients, except for multifidus at spinal level T12 (p = .01). However, when we analyzed the two sub groups, according to disease severity, FF% increased in the lesser severely affected group at L4/L5 erector spinae (p = .047), sartorius (p = .028), gracilis (p = .009), tibialis anterior (p = .047), peroneals (p = .028), and gastrocnemius medialis (p = .009), while the severely affected group only increased significantly at T12 multifidus (p = .028) and T12 erector spinae (p = .011). No difference in muscle strength was observed in the two subgroups. Conclusion: Our results add to the existing knowledge about the natural rate of disease progression in BMD. As quantitative MRI was able to identify changes where strength assessment was not, MRI could be a strong biomarker for change in BMD. However, our findings show that it is important to stratify patients with BMD according to phenotype for future clinical trials.